Detection of suicide among the elderly in a long term care facility - Tinakon Wongpakaran (2018)
Purpose: The aim of this study was to establish the level of correlation between the suicide item contained within the Core Symptom Index (CSI), and the presence of suicidal thoughts as assessed by the Mini-International Neuropsychiatric Interview (MINI) and the Cornell Scale of Depression in Dementia (CSDD). Patients and methods: Seventy elderly residents in a long term care facility were included in this study. All of these patients completed a CSI and a geriatric depression scale (GDS), plus were interviewed using CSDD, MINI (suicide module), and MMSE. Test characteristics of item two of the CSI (suicidal thoughts) and MINI were compared. Gwet's AC1 and Cohen's Kappa were also used to test the level of agreement between raters, and univariate analysis was used to determine predictors for the severity of any suicidal thoughts present. Results: There was found to be a significant correlation between suicidal ideation, as assessed by item two of the CSI, and the suicidal ideation score as assessed by MINI and CSDD (r=0.773 and r=0.626, P<0.001, respectively). The level of agreement across all three instruments was good (Gwet's AC1 =0.907). The CSI yielded a high level of sensitivity (100%) and specificity (90.32%) for suicidal thoughts as measured by MINI, with an area under the curve of 97%. When assessing predictors of the severity of suicidal thoughts, only item two of the CSI predicted severity, while the depression, GDS, and total scores obtained from the CSI did not. Conclusion: CSI item two has the ability to detect suicidal ideation, regardless of whether the patient has cognitive impairment and/or depression or not, and is currently the best predictor of its presence. Therefore, it shows promise as a measure for screening the presence of suicidal thoughts among the elderly in long term care facilities. © 2013 Wongpakaran and Wongpakaran.